ANALYSIS OF SOCIOECONOMIC STATUS, PARENTING STYLE, AND ENVIRONMENT ON EARLY CHILDHOOD DEVELOPMENT - Yudha, Rivo Panji; Shofa, Shofa (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
The purpose of this study was to analyze the influence of economic background, upbringing, and environment on the development of early childhood students of class B Kindergarten in the Takakan District, Serang City. This research is categorized as explanatory research, namely research that aims to explain the causal relationship between variables through hypothesis testing. The population in this study were students of TK B group who were in Takakan District, Serang City. There are 12 kindergartens in Takakan District with a total of 507 students. The sample in this study amounted to 51 people. Research variables in path analysis are divided into independent variables (Independent Variable) and dependent variables (Dependent Variable). The results showed that in total there was no significant and positive effect of Economic Background on the Environment with a P-Value of 0.054 > 0.05. 2. The results show that in total there is no significant and positive effect of Economic Background on Early Childhood Development with a P-Value of 0.595 > 0.05. 3. The results show that in total there is a significant influence and positive value of Family Parenting Style on the Environment with a P-Value of 0.000 <0.05. 4. The results show that in total there is no significant and positive effect of parenting style on early childhood development with a P-value of 0.746 > 0.05. 5. The results show that in total there is a significant and positive influence of the Environment on Early Childhood Development with a P-Value of 0.746 > 0.05.